Analisis Penerapan Manajemen Perubahan: Studi Kasus Pada UMKM Mie Uda Bro, Lubuk Begalung, Padang. - Amanda Putri Rahayu; Dinda Alya; Maharani Gabriella Rifera; Ramdani Bayu Putra; Zulfajri Zulfajri (CV. ITTC INDONESIA, 2025)
This study aims to examine the impact of implementing various changes implemented by the company on employees of the MSME